2015
DOI: 10.1016/j.scitotenv.2014.08.114
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide concentrations in frog tissue and wetland habitats in a landscape dominated by agriculture

Abstract: Habitat loss and exposure to pesticides are likely primary factors contributing to amphibian decline in agricultural landscapes. Conservation efforts have attempted to restore wetlands lost through landscape modifications to reduce contaminant loads in surface waters and providing quality habitat to wildlife. The benefits of this increased wetland area, perhaps especially for amphibians, may be negated if habitat quality is insufficient to support persistent populations. We examined the presence of pesticides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 67 publications
4
88
1
Order By: Relevance
“…Flusilazole, like other triazole fungicides acts by interrupting the formation of fungal cell walls through inhibition of sterol-14α-demethylase (CYP51), which is highly conserved across taxa including animals, where it is utilised in the pathway to cholesterol formation; thus effects on cell membranes may not be restricted to the target species (Bossche et al, 1995;Zarn et al, 2003). The hazards posed by triazoles to wildlife is because their effects may not be limited to CYP51, and there is emerging evidence that they may accumulate in the tissues of amphibians, (Hansen et al, 2014;Poulsen et al, 2015;Smalling et al, 2013), although this may vary depending on the levels found in the environment (Smalling et al, 2015). At low levels of exposure, triazole fungicides have been associated with endocrine disruption, disrupting steroidogenesis in adult male frogs at concentrations as low as 1 µg/L (Poulsen et al, 2015), as well as developmental defects in tadpoles and embryos (Bernabò et al, 2016;Di Renzo et al, 2011;Groppelli et al, 2005;Papis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flusilazole, like other triazole fungicides acts by interrupting the formation of fungal cell walls through inhibition of sterol-14α-demethylase (CYP51), which is highly conserved across taxa including animals, where it is utilised in the pathway to cholesterol formation; thus effects on cell membranes may not be restricted to the target species (Bossche et al, 1995;Zarn et al, 2003). The hazards posed by triazoles to wildlife is because their effects may not be limited to CYP51, and there is emerging evidence that they may accumulate in the tissues of amphibians, (Hansen et al, 2014;Poulsen et al, 2015;Smalling et al, 2013), although this may vary depending on the levels found in the environment (Smalling et al, 2015). At low levels of exposure, triazole fungicides have been associated with endocrine disruption, disrupting steroidogenesis in adult male frogs at concentrations as low as 1 µg/L (Poulsen et al, 2015), as well as developmental defects in tadpoles and embryos (Bernabò et al, 2016;Di Renzo et al, 2011;Groppelli et al, 2005;Papis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of agrichemicals are not typically measured in environmental compartments and instead much lower concentrations, often in complex mixtures tend to be detected, therefore amphibians are likely to be exposed to multiple agents in the environment (Khamis and Heikkila, 2013;Relyea, 2009;Smalling et al, 2015). Thus, in order to represent a more environmentally-realistic scenario, cells were also exposed to binary mixtures of flusilazole and carbendazim.…”
Section: Discussionmentioning
confidence: 99%
“…Wood frog populations inhabit pond ecosystems that can encounter pesticides following direct application, runoff, or aerial drift (Smalling et al., 2015). Using 15 populations in northwestern Pennsylvania (Hua et al., 2013, 2014, 2015), we found that populations living close to agriculture have higher baseline tolerance to a common acetylcholineesterase (AChE) inhibiting pesticide (carbaryl) compared to populations living far from agriculture (Hua et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…5,10,17,18 Neonicotinoids are frequently applied in spring as soil or seed treatments or in summer as a foliar spray. As seed treatments, they act as a systemic which protects the roots and shoots of young plants against piercingsucking insects such as aphids, thrips, and some Coleopteran pests (e.g., wireworm).…”
Section: ■ Introductionmentioning
confidence: 99%